Recurrent non-parasitic hepatic cyst with jaundice: a case report - Pukalendiran, Vigneshwaran; Samuel, Robinson Smile; Tirougnanassambandamourty, Tirou Aroul (International Surgery Journal, 2025)
The prevalence of simple hepatic cyst is 5-10% worldwide and usually does not require surgical intervention unless the patient becomes symptomatic. After laparoscopic surgical treatment there is a high chance of recurrence. Recurrence have been treated on individual basis by different centers either by laparoscopy or open cystectomy. A case of recurrent simple cyst of liver with obstructive jaundice in a 42-year-old lady treated by open cystectomy is presented.